Mental health burden in progressive pulmonary fibrosis and idiopathic pulmonary fibrosis: Depression and anxiety - Javorac, Jovan; Živanović, Dejan; Miladinović, Miljana; Mikić, Andrijana; Dukanac, Vesna; Ilić, Miroslav; Milenković, Ana; Peričević Medić, Sonja; Popović, Tamara; Kašiković Lečić, Svetlana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Progressive pulmonary fibrosis (PPF) is an umbrella term for several interstitial lung diseases characterized by the progressive proliferation of fibrous tissue within the lung interstitium. This study aimed to assess the prevalence of depressive and anxiety symptoms among PPF patients and their repercussions on quality of life. Methods: Thirty-seven PPF patients undergoing treatment at the Institute for Pulmonary Diseases of Vojvodina, Serbia were enrolled. The SGRQ questionnaire assessed quality of life, while the DASS-21 questionnaire evaluated anxiety and depression symptoms. Sociodemographic and clinical factors were correlated with questionnaires outcomes, and the influence of anxiety and depression symptoms on quality of life was examined. Results: Anxiety symptoms were detected in 56.75% of PPF patients and were more prevalent in patients previously diagnosed with depression and/or anxiety. Depression symptoms were detected in 45.95% of PPF patients and were more pronounced in the patients with longer duration of PPF, and positive history of malignancies. Stress symptoms were linked to lower PaO2 values and were detected in 37.84% of participants. HRQL was moderately to severely decreased and was lower in patients who, in addition to PPF, also suffered from other respiratory diseases, and was statistically significantly associated with lower DLCO values. A statistically significant correlation has been proven between the presence of anxiety, depression, and stress symptoms and HRQL, as measured through the "Symptoms" and "Impact" subscales of the SGRQ questionnaire. Conclusions: Anxiety and depression symptoms are highly prevalent among PPF patients, exerting substantial impacts on their quality of life.